Antibiotic Prescribing in Outpatient Children: A Cohort From a Clinical Data Warehouse. (June 2019) - Grammatico-Guillon, Leslie; Shea, Kimberly; Jafarzadeh, S. Reza; Camelo, Ingrid; Maakaroun-Vermesse, Zoha; Figueira, Marisol; Adams, William G.; Pelton, Steve
Aim . To characterize antibiotic (ab) prescriptions in children. Methods . Evaluation of outpatient ab prescriptions in a 3-year cohort of children in primary care using a data warehouse (Massachusetts Health Disparities Repository) by comorbid conditions, demographics, and clinical indication. Results . A total of 15 208 children with nearly 120 000 outpatient visits were included. About one third had a comorbid condition (most commonly asthma). Among the 30 000 ab prescriptions, first-line penicillins and macrolides represented the most frequent ab (70%), followed by cephalosporins (16%). Comorbid children had 54.3 ab prescriptions/100 child-years versus 38.8 in children without comorbidity; ab prescription was higher in urinary tract infections (>60% of episodes), otitis, lower respiratory tract infections (>50%), especially in comorbid children and children under 2 year old. Ab prescriptions were significantly associated with younger age, emergency room visit, comorbid children, and acute infections. Discussion . A clinical data warehouse could help in designing appropriate antimicrobial stewardship programs and represent a potential assessment tool.